2022
DOI: 10.3389/fphys.2022.1033784
|View full text |Cite
|
Sign up to set email alerts
|

Class of hemorrhagic shock is associated with progressive diastolic coronary flow reversal and diminished left ventricular function

Abstract: Introduction: The relationship between coronary artery flow and left ventricular (LV) function during hemorrhagic shock remains unknown. The aim of this study was to quantify coronary artery flow directionality alongside left ventricular function through the four classes of hemorrhage shock.Methods: Following baseline data collection, swine were exsanguinated into cardiac arrest via the femoral artery using a logarithmic bleed, taking each animal through the four classes of hemorrhagic shock based on percent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We have used these techniques in swine weighing up to 90 kg. 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 If swine weighing less than 40 kg are used, we recommend imaging their external iliac artery diameter to confirm that it will support instrumentation. 29 , 30 We chose the gender of the animals based on availability and cost, and ultimately, only male animals were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…We have used these techniques in swine weighing up to 90 kg. 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 If swine weighing less than 40 kg are used, we recommend imaging their external iliac artery diameter to confirm that it will support instrumentation. 29 , 30 We chose the gender of the animals based on availability and cost, and ultimately, only male animals were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there is sparse research investigating cardiac performance during diastole in response to hemorrhage (38) first reported coronary artery measurements in response to REBOA and found that the total coronary flows were almost three times higher during a full aortic occlusion than baseline, and subsequently decreased with a partial occlusion, proportional to increases in E es . Then, Elansary et al (46) examined the directionality of coronary artery flow waveform and LV function in progressive levels of hemorrhagic shock and found that the coronary arteries spent a greater proportion of diastole in retrograde flow. The findings from these studies indicate that future investigations incorporating both LV function and coronary flow would lead to a more holistic understanding of the underlying cardiovascular physiology of hemorrhagic shock and EHC interventions.…”
Section: Limitationsmentioning
confidence: 99%
“…The initial physiologic response to hemorrhage is the activation of the sympathetic nervous system, which regulates cardiac performance and vasoconstriction to maintain blood pressure and preserve the perfusion of essential organs ( Koyama et al, 1988 ; Skoog et al, 1985 ). This is closely associated with diminished cardiac function, multi-organ ischemia ( Elansary et al, 2022 ; Kvarstein et al, 2003 ), and a triggered inflammatory cascade ( Hierholzer et al, 1998 ). The inability to recover cardiac function following hemorrhage leads to cardiovascular collapse and mortality ( Chatpun and Cabrales, 2011 ).…”
Section: Introductionmentioning
confidence: 99%